KAJIAN POTENSI DAN PELUANG EKSPOR ROTAN INDONESIA (Study on the potential and opportunity of Indonesian rattan export) - Kirsfianti L Hariwibowo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The purpose of this Study 18 to obtain information concerning the Indonaian rattan market share and analyze a .trategy needed for developing market in effort to increase lndonaian share in world market.The analysis reveal that current lndonaian market hare iB mil.relatively low (< 19'); and the billlat ah.are iB on the commodity group which hOB tlte loweat market pofential t.e. inatti111/lampitof rattan. In (act other commodi group uch aa iattan furniture, and baketry have a wider market to panetrate. The availability of raw material, as suaeeted by thiB lhuly convinca the poaibility of eJOf)anding the rattan indudrie& .7b develop lndoneSian market hare, however, the following factors are needed to emphasize : (1) e:Kport priority ahould be foc.,;..d on to •the llighut co111uming country, (2) the quality of product. should be improved and (3) in the lorwer term. to broaden international market network.